Pediatric Solid Tumors in Resource-Constrained Settings: A Review of Available Evidence on Management, Outcomes, and Barriers to Care - Nicholas H. Carter; Andrew H. Avery; Jaime Libes; Harold N. Lovvorn; Erik N. Hansen (MDPI AG, 2018)
International disparities in outcomes from pediatric solid tumors remain striking. Herein, we review the current literature regarding management, outcomes, and barriers to care for pediatric solid tumors in low- and middle-income countries (LMICs). In sub-Saharan Africa, Wilms Tumor represents the most commonly encountered solid tumor of childhood and has been the primary target of recent efforts to improve outcomes in low-resource settings. Aggressive and treatment-resistant tumor biology may play a role in poor outcomes within certain populations, but socioeconomic barriers remain the principal drivers of preventable mortality. Management protocols that include measures to address socioeconomic barriers have demonstrated early success in reducing abandonment of therapy. Further work is required to improve infrastructure and general pediatric care to address disparities.